The Sphagnome Project: enabling ecological and evolutionary insights through a genus‐level sequencing project. Issue 1 (27th October 2017) - Weston, David J.; Turetsky, Merritt R.; Johnson, Matthew G.; Granath, Gustaf; Lindo, Zoë; Belyea, Lisa R.; Rice, Steven K.; Hanson, David T.; Engelhardt, Katharina A. M.; Schmutz, Jeremy; Dorrepaal, Ellen; Euskirchen, Eugénie S.; et al.
Summary: Considerable progress has been made in ecological and evolutionary genetics with studies demonstrating how genes underlying plant and microbial traits can influence adaptation and even 'extend' to influence community structure and ecosystem level processes. Progress in this area is limited to model systems with deep genetic and genomic resources that often have negligible ecological impact or interest. Thus, important linkages between genetic adaptations and their consequences at organismal and ecological scales are often lacking. Here we introduce the Sphagnome Project, which incorporates genomics into a long‐running history of Sphagnum research that has documented unparalleled contributions to peatland ecology, carbon sequestration, biogeochemistry, microbiome research, niche construction, and ecosystem engineering. The Sphagnome Project encompasses a genus‐level sequencing effort that represents a new type of model system driven not only by genetic tractability, but by ecologically relevant questions and hypotheses.